Innovative Strategies for Billing Automation: Bridging Revenue Cloud and Customer Experience in Enterprise Systems - Gurramkonda, Raziya Sulthana (International Journal of AI, BigData, Computational and Management Studies, 2026)
In enterprise environments, billing is no longer a purely financial operation confined to back-office systems. As organizations adopt subscription-based, usage-driven, and hybrid revenue models, billing interactions increasingly shape customer trust, satisfaction, and retention. Despite this shift, many billing automation initiatives continue to prioritize internal efficiency over customer experience, resulting in opaque invoices, frequent disputes, and manual corrections that undermine confidence in revenue processes. This paper examines innovative strategies for billing automation that bridge the gap between Revenue Cloud platforms and customer experience expectations. Drawing from hands-on enterprise implementations, the discussion focuses on practical automation patterns that improve transparency, flexibility, and governance without compromising financial accuracy or compliance. Rather than presenting billing automation as a standalone technical solution, the paper positions it as a strategic capability that directly influences long-term customer relationships and revenue stability.